Clarifying the Role of Urodynamics in the Preoperative Evaluation of Stress Urinary Incontinence - Sophie G. Fletcher; Gary E. Lemack (The Scientific World Journal)
It has not yet been definitively demonstrated that preoperative evaluation of women with stress urinary incontinence (SUI) with urodynamic testing (UDS) enhances surgical outcomes. Nonetheless, UDS is frequently utilized in the assessment of women with SUI in the hopes that results will shed light on preoperative risk factors for failure or postoperative voiding dysfunction. Poorer outcomes for stress incontinence surgery are primarily attributed to intrinsic sphincter deficiency (ISD), detrusor overactivity (DO), and voiding dysfunction. The ability of UDS to identify and characterize those parameters reliably remains under investigation. Furthermore, debate continues regarding the association of each of those factors with postoperative success for various SUI procedures. Since UDS is invasive, costly, and not always available, it is imperative that its benefit be carefully explored. In this review, we discuss the value of UDS in identifying risk factors for poor outcome and how those risk factors are associated with surgical failure.